PENGARUH PENGETAHUAN AWAL TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK PADA TEMA PANAS DAN PERPINDAHANNYA DI KELAS V SD - Sun Dahry; Aldora Pratama (Universitas Muhammadiyah Makassar, 2021)
The purpose of this study was to investigate: the effect of initial knowledge on critical thinking skills of students. This research is a quasi experimental research. The population is all students at SD Nanggalo Tarusan Pesisir Selatan and the sample is 50 students in class VA and VB. This sampling technique is porpusive sampling. The data from the research results were obtained from tests of preliminary knowledge and tests of critical thinking skills. The results showed that the students' initial knowledge influenced the critical thinking skills of students. There is no significant difference between critical thinking skills and high initial knowledge thitung =1,87 ttabel = 2,56; Critical thinking skills with lower initial knowledge are higher t hitung =3,71 t tabel = 2,56.